Psychological and neuropsychological status of patients with both blast-related ocular injury and mild traumatic brain injury late after the traumatic event (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To determine the psychological and neuropsychological status of patients with both blast-related ocular injury and mild traumatic brain injury (TBI) late after the traumatic event.Material and Methods: Thirty patients with blast-related ocular injury, reduced visual function and comorbid mild TBI were included in the study. The following methods of psychological and neuropsychological assessment were used: formalized interview; Suicidality, Post-traumatic Stress Disorder (PTSD), Alcohol Dependence, and Drug Dependence scales of the Mini-International Neuropsychiatric Interview (MINI); Raven’s Progressive Matrix scale; Personal and Social Performance (PSP) scale; PROMIS® Pain-Interference scale; Hospital Anxiety and Depression Scale (HADS); Mazes subtest of the Neuropsychological Assessment Battery (NAB); and Repeatable Battery for the Assessment of Neuropsychological Status (RBANS).Results: The following significant correlations were found: PSP functioning and support from the family (r = 0.533, p = 0.002); total RBANS score and Mazes subtest score (r = 0.466, p = 0.009); total RBANS score and self-reported stress score (negative correlation, r = -0.492, p = 0.006); HADS depression and self-reported stress score (r = 0.646, p = 0.000114); PROMIS pain scale and PTSD scale (r = 0.482, p = 0.007). No association was found between the number of mild TBI events experienced and neuropsychological and psychological measurements.Conclusion: Blast-related mild TBI concomitant with ocular injury has a substantial and long-term impact on casualty’s cognitive and psychological functions. In such patients, the most prominent cognitive deficits occur in the domain of executive function (including cognitive control and planning and problem-solving skills). In the presence of reduced visual function, these deficits have a substantial impact on total cognitive scores, scores of other psychic functions (namely, attention and memory) and significantly affect the patient’s capacity for independent functioning.
Keywords: blast-related ocular injury; mild traumatic brain injury; neuropsychology; clinical psychology; post-traumatic stress disorder